Community Translanguaging Through Amistades: Holistic Support for Latina Mothers and Their Children’s Kindergarten Readiness - Lee, Sophia Piral; Rueda Varon, Jenifer (International Electronic Journal of Elementary Education, 2026)
This collaborative (auto)ethnographic study documents the use of community translanguaging within a support group called Amistades (pseudonym) created through a community-based partnership between mamás Latinas and a local non-profit organization. The purpose of Amistades was to offer parental and childhood socioemotional and educational support for early childhood and kindergarten readiness in a predominantly white and English-speaking city in the U.S. Amistades was exclusively designed for mamás Latinas and their young children (0-5 years old), creating unique safe spaces where mothers could share and appreciate their mujerismo, Latinidad, migration experience, translanguaging (English-Spanish), and pedagogies of the home to support their children’s identity, multiculturalism, bilingualism, and protection after migrating. Co-facilitating the support group for two years, we–two mamás Latinas–documented our experience with living and interacting in a new community, mainly including community translanguaging and supporting each other in constant pláticas, monthly support groups with other mothers, playdates with our children, and the use of social media. Then, we followed a grounded theory approach to reflect on and interpret the data. Finally, we reflected on how community translanguaging helped Amistades: (1) become our only red de apoyo and sentido de comunidad with other familias Latinas; (2) allow mothers to share their experience, leadership, and diverse resources supporting other families to navigate and thrive as peers; (3) create spaces where young children could meet and interact with their monolingual Spanish-speaking and bilingual friends through free play; and (4) provide mothers with emotional support, knowledge, and resources to enroll their children in kindergarten and navigate elementary schools for the first time. This study has implications for research-practice partnerships by informing how elementary schools and other local organizations and researchers can address critical gaps in supporting familias Latinas, protecting and promoting their multiple identities and languages, amistades, and liderazgo to navigate elementary schools in the U.S. through community translanguaging.